2012
DOI: 10.1007/s00586-012-2370-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for major peri-operative complications in adult spinal deformity surgery: a multi-center review of 953 consecutive patients

Abstract: Purpose Major peri-operative complications for adult spinal deformity (ASD) surgery remain common. However, risk factors have not been clearly defined. Our objective was to identify patient and surgical parameters that correlate with the development of major peri-operative complications with ASD surgery. Methods This is a multi-center, retrospective, consecutive, case-control series of surgically treated ASD patients.All patients undergoing surgical treatment for ASD at eight centers were retrospectively revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
89
5
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(105 citation statements)
references
References 30 publications
4
89
5
7
Order By: Relevance
“…Some authors have reported on specific complications like surgical site infection rate in adult deformity approaching 5.5 % with deep infection being 3.5 % [16]. Schwab et al [17] reported major perioperative complication rate in the order of 8.4 %. Cho et al [18] reported major complications in 34.3 % of the patients undergoing revision deformity surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported on specific complications like surgical site infection rate in adult deformity approaching 5.5 % with deep infection being 3.5 % [16]. Schwab et al [17] reported major perioperative complication rate in the order of 8.4 %. Cho et al [18] reported major complications in 34.3 % of the patients undergoing revision deformity surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These are all performed by a posterior approach and rely on solid pedicle instrumentation -two to three levels above and below -to obtain immediate corrective power, unfortunately at the expense of significant morbidity [5,11] . Major complications including death, permanent paralysis, pseudoarthrosis, proximal junctional failure and infection may affect up to 60% of treated patients and are largely dependent on age, degree of sagittal imbalance and medical comorbidities at the current state of knowledge [3][4][5][6]11] . In addition, there seems to be wide variability in revision rates among centers treating different volumes of patients [12] .…”
Section: Discussionmentioning
confidence: 99%
“…While the current scenario is dominated by the obsessive research of balance through the use of spinal osteotomies [7] , the next will see the research of lesser invasive methods of anterior and posterior reconstruction that would not be at the expense of obtaining a solid and lasting fusion [8] . Open questions are issues about costs and complications of this most complex aspect of clinical medicine [9][10][11] . Aim of this paper is to set the scene of current and future trends in adult spinal deformity (ASD) surgery by analysing the potentially most important recently published papers on the subject.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complication rates reported for these procedures range from 25 to 80 % [1,2]. Even for general spine surgery, intraoperative adverse event rates reported in the literature reach 10 % [3][4][5][6][7][8][9]. Complex spine surgery, defined as a surgical procedure requiring six or more levels of vertebral fusion, is typically used to correct adult lumbar scoliosis.…”
Section: Introductionmentioning
confidence: 99%